2015
DOI: 10.1007/978-3-319-24932-2_5
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment of Lung Cancer and Therapeutic Implications

Abstract: The tumor microenvironment (TME) represents a milieu that enables tumor cells to acquire the hallmarks of cancer. The TME is heterogeneous in composition and consists of cellular components, growth factors, proteases, and extracellular matrix. Concerted interactions between genetically altered tumor cells and genetically stable intratumoral stromal cells result in an "activated/reprogramed" stroma that promotes carcinogenesis by contributing to inflammation, immune suppression, therapeutic resistance, and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 245 publications
1
92
0
Order By: Relevance
“…A large number of studies showed that cancer stromal cells, such as inflammatory cells, endothelial cells and fibroblasts, induced resistance to chemotherapy in lung cancer. 25 In the stromal cells, fibroblasts have been reported to be a main player in this phenomenon. 4,26 In the present study, we revealed that PAI-1 inhibition limited the chemotherapy resistance through suppressing the MF characteristics of CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies showed that cancer stromal cells, such as inflammatory cells, endothelial cells and fibroblasts, induced resistance to chemotherapy in lung cancer. 25 In the stromal cells, fibroblasts have been reported to be a main player in this phenomenon. 4,26 In the present study, we revealed that PAI-1 inhibition limited the chemotherapy resistance through suppressing the MF characteristics of CAFs.…”
Section: Discussionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for 80–85% of all lung malignancies and the overall 5-year survival of patients with NSCLC remains approximately 15–20% [3, 4]. Although the driver mutations including epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) have revolutionized the treatment and prognosis of NSCLC, it just focused on the cancer cell intrinsic properties [5, 6]. More and more recent studies have begun to investigate the prognostic and clinicopathological role of tumor microenvironment (TME) in NSCLC [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, it had been supposed that the tumorigenesis and failure of cancer immunotherapy was due to the insufficient activation of immune system. Recently, increasing evidence indicates that inhibitory function plays the crucial role in the TME [6, 9]. One of the most significant inhibitory components is the regulatory T cells (Tregs).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, tumor microenvironment induces immune suppression, reduces the efficacy of chemotherapy, and favors epithelial-to-mesenchymal transition (EMT) in the airways (type-II EMT, obliteration of small airways), which has recently emerged as a novel target for LC treatment (112). In line with this, a recent investigation showed that treatment of lung epithelial cells with CS extracts induced alveolar EMT through a cascade of biological mechanisms characterized by a rise in TGF-beta and Rac1/Smad2 signaling pathway (113).…”
Section: Chronic Inflammationmentioning
confidence: 99%